Comparison of Pharyngeal Airway Width among Individuals having Skeletal Class I Malocclusion with Different Growth Patterns (Orthodontic Journal of Nepal, 2022)
Introduction: An interaction can be seen between respiratory function and the maxillary growth pattern. Therefore, this study was conducted to assess and compare the pharyngeal airway width of individuals with different growth patterns in skeletal class I malocclusion.Materials and Method: Analytical cross-sectional study was done to assess total of 60 cephalometric radiographs of individuals with skeletal class I malocclusion pattern selected through convenience sampling method. McNamara analysis was done to measure the width of upper and lower pharyngeal space. Statistical analysis was done in SPSS version 20. One way ANOVA and Post Hoc test were done to determine the mean difference of upper and lower pharyngeal airway space width in between individuals of skeletal class I malocclusion with different growth pattern.Result: There was no significant mean difference in upper pharyngeal airway space (p=0.201) seen in between three growth patterns of individuals with class I malocclusion. However, the study participants with vertical growth pattern showed significantly less lower pharyngeal space width (8.36±2.63mm) than in horizontal growth pattern (10.89±3.46 mm, p=0.028).Conclusion: The findings of this study conclude that in skeletal class I malocclusion, there is no difference in upper pharyngeal space dimensions among individuals with different growth patterns but the vertical growth pattern shows smaller dimension of lower pharyngeal space than horizontal growth pattern.